Building a Learning Community in Liberia Through Partnerships at iCamp us - iCampus (USAID LEARN, 2018)
Accountability Lab Liberia (ALab) and iLab Liberia established iCampus - a shared innovation, co-working and community space for organization s focusing on the intersection of technology, accountability and socia l change in Liberia. ALab implements DAI’s Learning activities at iCam pus, and it is referred to as the Strategic Learning Partner of USAID Liberia Accountability and Voice Initiative (LAVI). LAVI is a five yea r USAID program with an overarching goal to strengthen multi-stakehold er partnerships to advocate for and monitor policy and accountability reforms. The iCampus CLA case scenario captures joint efforts of Accou ntability Lab Liberia, iLab Liberia and USAID LAVI, to ensure that lea rning and methodologies are shared and applied by development actors; address common capacity challenges that particularly hinder civil soci ety from engaging in evidence-based and issues-based advocacy using va rious approaches, including network-building, creation of a cross-sect oral learning space- through collaboration and learning. In 2017, iCam pus conducted a learning mapping survey to understand how organization s are learning in Liberia. The result indicated that frameworks and co ncepts of organizational learning are not yet well understood or used to guide strategic or programmatic practices, by either Liberian or in ternational organizations. ALab, iLab and USAID LAVI then adopted a se t of strategies, that led to the implementation of a CLA, enabling the establishment of the first multi-sectoral learning community in Liber ia.